Registros de Impuestos, Tasas y Contribuciones en el Departamento de Rentas del GAD Municipal de Puebloviejo Periodo 2017 – 2018 - Cortez Suárez, Madelaine Nicole (2020)
Tax collection in Ecuador represents one of the main sources of financing for state agencies. Currently, for the Decentralized Autonomous Governments, taxes, fees and contributions embody one of the revenues of their management, therefore the efficiency in the collection of these taxes leads to the development of their competences. This investigation has been directed to the Registries of Taxes, Rates and Contributions in the Revenue Department of the Municipal GAD of Puebloviejo Period 2017 - 2018. In this entity the values that are collected by said taxes show a decrease, one of the reasons is the default of payment by the taxpayer and the lack of requirement of the entity. All this leads to the accelerated increase in accounts receivable from previous years, which by not applying a mechanism that allows the recovery of the portfolio directly affects the self-management of the company. This study aims to know and analyze each of the critical points that lead to the decrease in the values that are estimated to be collected. For the development of this work, research techniques such as interview, observation and the information provided by the entity were used.